Knowledge of Overcoming Chemotherapy Side Effects on Breast Cancer Patients: The Impact of Audio-Visual Media - Rizka, Adi; Zara, Noviana; Zakiyya, Sarah (AVERROUS: Jurnal Kedokteran dan Kesehatan Malikussaleh, 2024)
Breast cancer is the most common type of cancer in women and the leading cause of death in Indonesia. According to 2020 data, there are approximately 42.1 breast cancer cases per 100,000 women. Chemotherapy is one of the most effective treatments for cancer. A lack of knowledge about how to deal with chemotherapy side effects can impair patient compliance with chemotherapy treatment. One of the health promotion media that can be utilized to share knowledge about how to control the side effects of chemotherapy is audiovisual media. The purpose of this study is to investigate the influence of audio-visual media on knowledge in overcoming chemotherapy side effects in breast cancer patients at Cut Meutia General Hospital, North Aceh. This study employed a quasi-experimental methodology with a one-group pretest-posttest design and included 66 breast cancer patients receiving chemotherapy at Cut Meutia General Hospital in North Aceh. A questionnaire about knowledge in combating chemotherapy side effects was utilized as the research instrument. The research findings were the level of knowledge of breast cancer patients before health promotion, which was in the good category for 41 people (62.2%), and after health promotion, which was in the good category for 66 individuals (100%). Based on the Wilcoxon test, the usage of audio-visual media has an effect on knowledge with a P of 0.000. The study's findings indicate that using audio-visual media as a learning tool will help breast cancer patients at Cut Meutia General Hospital, North Aceh and gain more knowledge about how to deal with the side effects of chemotherapy.